Keseimbangan antara Globalisasi dengan Kebutuhan Lokal dalam Praktik SDM - Kamandanu, Muhammad Aditya; Anshori, Mochammad Isa (Lembaga Yasin AlSys, 2025)
Globalization has fundamentally changed the human resource management (HR) landscape, creating complexity that requires organizations to develop adaptive strategies capable of bridging global practices with local needs. This research with a literature review aims to explore the dynamics of the balance between the demands of globalization and the local context in HR practices. The research provides comprehensive insight into HR strategies capable of bridging the gap between global demands and the uniqueness of local contexts, offering a conceptual framework for organizational navigation in the era of globalization. Findings reveal successful organizations of the future will be those that are able to develop flexible HR practices, which simultaneously meet global standards while remaining responsive to the needs of the local context.